Kawasan Perdesaan Ditinjau Dari Sistem Tata Air Daerah Aliran Sungai (DAS) - Roestam Sjarief (Journal of Regional and City Planning, 1997)
Water related issues in spatial planning, either for urban or rural areas, need to be addressed in the framework of riverbasin approach. Riverbasin as a geohydrologic system is considered as a proper region for planning and management of water resources. Water resources planning based on this riverbasin concept need to be integrated into a rural spatial planning. This paper discusses several issues related to the nature of riverbasin in relation with the spatial concept of rural areas, e.g. the basis of riverbasin approach, the nature of riverbasin as a geohydrological system, the management concept of riverbasin, the relationship between land use and the behaviour of riverbasin, the implication of riverbasin concept toward the spatial development of rural areas, and river protection in the rural spatial areas. It is concluded that the objective of riverbasin development and rural spatial development has a common ecological ground. It should play a great attention on the conservation function of the areas. However it is also important to take into account the diversification of options among the society that need to be directed in such that will lead to the optimal use of space and resources.